Genealogical Acculturation of Bali and Sasak Cultures in Lombok Island - Susilo Edi Purwanto; I Wayan Sutama (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
Harmonious life relations between Balinese and Sasaknese society in Lombok had been intertwined properly since the era of Karangasem Kingdom. Numerous historical heritages of both ethnics are founded in various places and still exist nowadays. Those ethnics concerned on the effort to build up a great civilization rather than making culture boundaries in the cultural diversity. The qualitative anthropologist approach was used in order to identify the elements of genealogical acculturation of Balinese and Sasaknese in Lombok. The data were reduced step-by-step and analyzed descriptively. The data were collected by employing participative observation technique, deep-structured interview, and documentary files. The results suggest that the genealogical acculturation of Balinese and Sasaknese were found out on the following elements: (1) mutually absorbed language, (2) conversance system by adopting the farming technique mutually, (3) social organization, both adopted patrilineal system, (4) living equipment system and technology, a harmonious and supporting linking between system of living equipment and technology, (5) livelihood system by adopting harmonious irrigation system, (6) religion system, there was an intensive acculturation from those ethnics to bear a new understanding of Sasaknese and some are adopted by Balinese, and (7) arts, the unification of both ethnics emerged novel arts.